Environmental studies : a practioner's approach - Arceivala, S.J (McGraw-Hill's AccessEngineering., 2012)
"Environmental Studies - A Practitioner's Approach is a dual purpose book. Firstly, it introduces the reader to the problems related to an urban environment which a young engineer would have to face in building up and maintaining its infrastructure for operating various services. Secondly, the book gives insights to the young engineers on how the environment is to be protected against pollution and degradation.".